Analyzing the observational capabilities of a Moon-based platform for monitoring Earth’s outgoing radiation - Guang Liu; Runbo Dong; Yin Jin; Mengxiong Zhou; Hanlin Ye; Rui Song; Jan-Peter Muller; Huadong Guo (Geo-spatial Information Science)
A Moon-based platform can observe the whole Earth’s disk instantaneously. This paper introduces a fully linked scheme to analyze the observational capabilities of Earth’s outgoing radiation from a Moon-based platform. Precise geometric model for the sensors, including a radiometer and a multi-spectral camera, is established at first. Subsequently, a new method for the reconstruction of the Earth’s outgoing radiation is proposed. We use the Goddard Earth Observing System Version 5 (GEOS-5) data as a reference to simulate the observation data from Moon-based sensors and carry out reconstruction to comprehensively assess the observational capabilities. The results show that: 1) the lowest daily ground coverage rate is about 88.8% and global coverage including polar regions can always be achieved within a month; 2) the sampling interval needs to be less than 4 hours to ensure the accuracy of reconstruction; 3) the image captured by a multi-spectral camera is capable of reconstructing the distribution of the Earth’s outgoing radiation, while the data obtained from a radiometer facilitates the reconstruction of the global Earth’s outgoing radiation, thereby enabling a comprehensive assessment of the Earth’s outgoing radiation. These findings offer valuable insights that can guide the design of sensor parameters for forthcoming missions.